2016
DOI: 10.1177/1098612x16645141
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of negative pressure wound therapy and silver-coated foam dressings in open-wound treatment in cats

Abstract: Objectives The objective of this study was to evaluate negative pressure wound therapy (NPWT) for the treatment of complicated wounds in cats. Methods Twenty cats undergoing open-wound treatment in two clinics were classed according to treatment method: NPWT (group A, n = 10) and polyurethane foam dressing (group B, n = 10). Pairs of patients from each group were matched based on wound conformation, localisation and underlying cause. Cats from both groups were compared in terms of duration of previous treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Arti et al [ 73 ] reported a 1.5 day reduction in the duration of hospital stay and 19% reduction in wound surface for patients receiving NPWT for skin graft or flap coverage as opposed to patients receiving conventional wound dressings. In a separate study, a 13.7 day reduction in the duration of wound closure for cats with open wounds was reported [ 74 ]. Additional studies examining treatment of open-wounds with NPWT against other conventional therapies could be beneficial in determining the effect of NPWT on wound closure duration.…”
Section: Vac Mechanisms Of Actionmentioning
confidence: 99%
“…Arti et al [ 73 ] reported a 1.5 day reduction in the duration of hospital stay and 19% reduction in wound surface for patients receiving NPWT for skin graft or flap coverage as opposed to patients receiving conventional wound dressings. In a separate study, a 13.7 day reduction in the duration of wound closure for cats with open wounds was reported [ 74 ]. Additional studies examining treatment of open-wounds with NPWT against other conventional therapies could be beneficial in determining the effect of NPWT on wound closure duration.…”
Section: Vac Mechanisms Of Actionmentioning
confidence: 99%
“…A few case reports, as well as retrospective and prospective studies in cats [17, 18] and dogs [1924] have already described the use of negative pressure to treat different types of wounds: traumatic wounds, burn injuries, infected surgical incision and skin grafts. In addition to occurring earlier, the granulation tissue filling a wound treated by NPWT in dogs has been noted to be smoother, not exuberant, and histologically demonstrates well-organized collagen fibers [20], suggesting a decreased likelihood for NPWT-treated wounds to develop EGT in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Nolff and colleagues retrospectively detected improved infection control and fewer cases with progressing signs of sepsis under NPWT compared with polyurethane foam treatment in dogs and cats. 11,12 But so far, there are no prospective randomized studies available to underline and quantify this effect. It is generally accepted that a wound is a local problem that should have little systemic impact, 1 which might be one of the reasons why systemic impacts of treatment are not frequently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies demonstrated that one of the main reasons for open wound treatment in dogs and cats is uncontrollable infection frequently linked with systemic signs of sepsis. 11,12 In contrast to chronic wounds of other origin, this subtype of wounds represents a group in which systemic effects frequently complicate the situation. Failure to control local and systemic infection are the main reasons for unsuccessful treatment of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation